Enhancing Self-Esteem and Satisfaction with Continuous Care Support during Childbirth: A Pre-experimental study - Sharmila Samson jayaprakash,; Sumathi Chandran,; Shankar Shanmugam Rajendran,; Vanitha Narayanasamy Naidu,; Meenakshi Prabhakar,; Kalvikkarasi Narayanaswamy,; Tamilthendral Ravikumar, (The Bioscan, 2025)
Childbirth, especially for first-time mothers, is both a physically demanding and emotionally charged experience. Continuous care support by a trained caregiver from the active phase of labor until the early postpartum period is known to positively influence birth outcomes, maternal satisfaction, and psychological well-being. Objectives: 1. Assess the pre-test self-esteem and satisfaction levels among primigravida mothers. 2. Evaluate the effectiveness of continuous care support. 3. Compare pre- and post-test levels of self-esteem and satisfaction. 4. Determine the association between post-test scores and selected demographic/obstetric variables. Materials &Methods: A pre-experimental one-group pre-test post-test design was employed at a tertiary care maternity hospital in Chennai. A total of 60 primigravida mothers in active labor were selected using convenience sampling. Intervention included continuous emotional, physical, and informational care by a nurse researcher from 4 cm dilation through 2 hours post-delivery. Data were collected using the Rosenberg Self-Esteem Scale and the Client Satisfaction Questionnaire (CSQ-8). Result and Discussion: - Pre-intervention: 60% had low self-esteem; 56.7% had moderate satisfaction. - Post-intervention: 70% had moderate and 30% high self-esteem; 60% had high satisfaction. - Mean self-esteem increased from 2.45 to 3.75 (p<0.001); satisfaction from 2.3 to 3.7 (p<0.001). - Significant associations: Self-esteem with age (p=0.004), duration of marriage (p=0.045), and mode of delivery (p=0.012); Satisfaction with education, immunization status, and maternal illness. Conclusion: Continuous care support is a highly effective, low-cost intervention that significantly improves maternal self-esteem and satisfaction. Its integration into routine labor care could transform maternity practices toward more holistic and respectful childbirth experiences.